Development of double surface acoustic wave resonator system for hydrogen nd ammonia gas sensing - Yunusa, Zainab (2015)
Acoustic wave technology has been used for gas sensing applications for several decades. A SAW device consists of a piezoelectric substrate; inter digital transducers (IDTs) and reflectors. Rayleigh waves have two types of configuration namely SAW resonator and SAW delay line. Each configuration has different structure but has similar output characteristic when employed as a sensor. The Surface Acoustic Wave (SAW) sensor has offered the development of small, lightweight, battery-free, maintenance free and multiple sensor wireless interrogation operation. Double SAW resonator (DSAWR) is a configuration that involves two SAW resonators and it has proven to be reliable in sensing applications such as temperature and strain sensor. Carbon nanotubes (CNTs) have been proven to be good sensing material with high metallic behavior. However, when they are employed as sensing materials for SAW gas sensor they cause short circuit to the IDTs. Previous works based on single SAW resonator gas sensor requires the fabrication of a guiding or protective layer which is made up of oxides so as to avoid the short circuiting of the IDTs. Based on literature reviewed, previous works have employed the DSAWR for strain and temperature sensors but it has never been deployed for gas sensing. Therefore, in this thesis, DSAWR resonator based gas sensor was developed and been deployed for gas sensing applications for the first time. The advantage of this technique is that the CNT sensor was fabricated and integrated independently which eliminates fabrication of any guiding or protective layer for the SAW resonator. Another advantage of this technique is that the same system could be used with different types of sensing layer which makes it more economical and less time consuming. In this thesis the Double Surface Acoustic Wave Resonator System (DSAWR) for gas sensing application was proposed and developed. DSAWR system consists of two commercial SAW resonators with resonant frequencies of 433.92 and 433.42 MHz. The DSAWR system was fabricated on a PCB and deployed for gas sensing application. There are 2 types of system that were used for DSAWR gas sensing application but the systems differ in the sensing material been employed and is been configured as system 1 and system 2 sensors. System 1 sensing layer composed of functionalized multi walled carbon nanotubes with polyaniline layer which was deployed for hydrogen sensing while system 2 sensing layer composed of polyaniline as a sensing material and was deployed for ammonia sensing. Results obtained showed that system 2 sensor was better than system 1 sensor in terms of sensitivity. The sensitivity of system 1 sensor was found to be 3Hz/ppm at room temperature while it doubles to 6 Hz/ppm at 40 0C. System 2 sensing results obtained showed that the system has detection limit of 0.125 % with a sensitivity of 8 Hz/ppm at room temperature. In order to investigate the sensing behavior of a new material, system 3 sensor was developed which is based on Graphene Nanoribbon (GNR) and was deployed for ammonia sensing. Results obtained showed that the novel structure could be a potential material for ammonia sensing with good sensitivity and a detection limit of 1250 ppm.